O papel das emoções na deliberação : o debate sobre a redução da maioridade penal no Brasil - Gabriella Hauber Pimentel (2015)
This research discusses how emotions relate to arguments against and in favor of the reduction of the minimum age of criminal responsibility in Brazil and what they reveal about the way the adolescents are seen and perceived. The role of emotions is a controversial issue in deliberation studies and yet not explored enough empirically. Our analysis is carried out from three deliberative arenas: public hearings and meetings in the National Congress, a Facebook page (18 Reasons) and news published by UOL portal, in the years 2013 and 2015. Much of the work that seek to grasp the emotions empirically adopts a lexicon criteria (word identification) or apply questionnaires to participants in a deliberative process. The material we set out to analyze doesn't allow us to use such methods, só we created four categories of emotions expression (anger/hate, compassion, fear, and anger). We seek to associate the speech acts with these emotions. To develop our analysis we departed from the studies on deliberative system, emotion and deliberation. As a methodological option, we did a systematic qualitative analysis of the material collected in the three proposed environments. The units of analysis are the speech acts, which are analyzed according to the following categories: i) type of emotion mobilized; II) to whom the emotion is intended; III) relation to the arguments circulating in the public sphere; and IV) characterization of the adolescents. In our analysis, we found out that the same emotion can show up in arguments against and in favor of the reduction and that the target object is the main difference between these positions. Thus, we seek in our work to deny the dichotomy between reason and emotion and avoid classifying emotions as positive or negative, and to discuss how the different settings of the environment relates to the expression of emotions.